Evaluasi Penerapan ISO 14001:2015 di PT. X - Steven Willy Susanto; Nova Sepadyati (Jurnal Titra, 2022)
Fierce competition in winning consumers on the sale of polyethylene-based products causes PT. X has to continuously update the ISO 14001:2015 environmental management system certification. PT. X strives to maintain the implementation of the environmental management system, therefore an analysis of the application of the ISO 14001: 2015 environmental management system is carried out. It aims to obtain the degree of conformity between the actual conditions in pt. X with existing standards in the ISO 14001:2015 environmental management system and found a draft of improvements to improve the level of conformity. The methods used in this study are filling in iso 14001: 2015 checklists, calculating the percentage of the degree of conformity with the gap analysis method, root cause analysis with the five why method and fish-bone diagram. The results of this study are an improvement design that is expected to be useful by PT. X to meet the requirements for renewal of ISO 14001:2015 environmental management system certification.